Hobbes's philosophy of religion - Holden, Thomas (Oxford University Press, 2023)
"Hobbes's Philosophy of Religion presents a new scholarly interpretation of Hobbes's treatment of religious speech and practice. It argues that the key to Hobbes's treatment of religion is his theory of religious language. According to Hobbes, the proper function of religious language is not to describe, state facts, or affirm truths. Instead, such talk ought only to express attitudes of honour, reverence, and humility before the incomprehensible great cause of nature. His theory valorises the traditional discourses of theism, natural religion, and revealed religion, but only as an expression of reverence without descriptive import. Hobbes is sincerely pious, rejecting atheism and irreligion. But he also rejects literal-minded theism, and any realist conception of the divine attributes. The book provides a comprehensive study of Hobbes's highly original treatment of religion. It also offers an integrated account of Hobbes's philosophical thought around religious topics. The account brings out the connections between Hobbes's theoretical philosophy - including his philosophy of mind, language, and human nature - and his practical religious politics, including his views on religious toleration, ecclesiology, and the religious function of the civil state--